Telaah Pemikiran Al Kindi: Konsep Ketuhanan dalam Prespektif Islam - Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti; Fauzi, Sriyono (AHKAM, 2024)
Al-Kindi lived at a time when philosophy was not yet well known in the tradition of Islamic thought, precisely during the transition from traditional theology to philosophy. Al-Kindi was the first Arab to introduce philosophy into Arab thought and was given the title "Philosopher of the Arab Nation". Al-Kindi brought together religion and philosophy on the basis of the consideration that both are sciences of truth, so that there is no difference between the two. The influence of the Mu'tazilah group was clearly visible in his way of thinking when he determined the ability of the human mind to know the secrets brought by the Prophet Muhammad saw. The first philosophical science which includes divinity, oneness, primacy, and other sciences which teach how to obtain useful things and get rid of harmful things was also brought by God's apostles.